(untitled) (Journal of Governance and Development (JGD), 2022)
Reaching the endemic phase of COVID-19 starting April 1, 2022, Malaysia had move forward for their normal norm. No more home isolation and even mask mandate is unnecessary. With the vaccination status (completed 2nd dose), people can freely access the premises. However, Ministry of Health did not take COVID-19 for granted. The ministry keeps updating daily new cases to remind public the urgency to prevent the COVID-19 outbreak. This study describes the vulnerability of the COVID-19 outbreak in Malaysia by assessing relationship between the vaccination status to the number of COVID-19 cases. The data is taken from the ministry and panel data is taken to test within the period of endemic phase (April 2022- June 2022). The key findings will provide the relationship between the access variables and further research should be conducted to provide relevancy of this matter especially during endemic phase.